Coulomb effects in cold fission - Montoya, Modesto (1986)
The structures in the mass and total kinetic energy (TKE) distributions in cold fission of U-234 and U-236 are interpreted in terms of the Coulomb interaction energy (C) between fragments at the scission point. The maximal value of C (Cmax) corresponding to the most compact scission configuration, is calculated for several mass fragmentations. It is shown that Cmax increases, if one increases the charge asymmetry for a given primary fragmentation and Q being constant. This dependence produces oscillations with a period of approximately 5 amu of C as a function of the light fragment mass which are correlated with the observed oscillations of the maximal value of TKE. Moreover, it follows that the yields of the more asymmetric charge fragmentation of the same system are increased, that is for the more compact configuration.